Transitions in modes of coastal adaptation: addressing blight, engagement and sustainability - Brown, Sally; Tompkins, Emma L.; Suckall, Natalie; French, Jon; Haigh, Ivan D.; Lazarus, Eli; Nicholls, Robert J.; Penning-Rowsell, Edmund C.; Thompson, Charlie E. L.; Townend, Ian; van der Plank, Sien (Frontiers in Marine Science, 2023)
Coastal defences have long provided protection from erosion and flooding to cities, towns and villages. In many parts of the world, continued defence is being questioned due to both environmental, sustainability and economic considerations. This is exemplified in England and Wales, where strategic Shoreline Management Plans envisage realignment of many protected coasts, often with low population densities, over the coming decades. The policy transition from protection to realignment is often resisted by affected communities and can have high political costs. Whilst some preparations for such transitions have been made, the communities affected are often not fully aware of the implications of policy change, and this brings the potential for blight. In this paper, we investigate the challenges of implementing transitions in coastal policy within England and Wales. The analysis is based on data obtained from three workshops held in 2019 that were attended by council members, engineers, planners, scientists and other relevant professionals. Five conditions are found to promote contention: (i) policy actors with competing priorities and different decision making time frames (immediate to decadal to a century); (ii) divergence between regulations and ad hoc political decisions (e.g. in relation to the demand for new housing); (iii) limited or non-existent funding to support policy transition; (iv) community expectation that protection is forever; and (v) a disconnection between people and ongoing coastal change. Our research indicates that transitions can be better supported through: (1) integrated multi-scalar preparedness for coastal change; (2) an accessible evidence base and future vision to nurture political confidence in adaptation; and (3) defined, time-bound and accessible diverse funding streams to achieve transitions. Critically, these generic actions need to be embedded within the local political and planning system to facilitate transition to more sustainable coasts and their communities.